2009
DOI: 10.1111/j.1365-2796.2008.02062.x
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe monotherapy for cholesterol lowering in 2,722 people: systematic review and meta‐analysis of randomized controlled trials

Abstract: Abstract. Pandor A, Ara RM, Tumur I, Wilkinson AJ, Paisley S, Duenas A, Durrington PN, Chilcott J (University of Sheffield, Sheffield; and University of Manchester, Manchester; UK). Ezetimibe monotherapy for cholesterol lowering in 2,722 people: systematic review and meta-analysis of randomized controlled trials. J Intern Med 2009; 265: 568-580.Objectives. To study the evidence on the efficacy and safety of ezetimibe monotherapy for the treatment of primary (heterozygous familial and non-familial) hypercholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(105 citation statements)
references
References 43 publications
3
95
1
6
Order By: Relevance
“…Ezetimibe has slight positive effects in lowering plasma fasting TG (8%) [153]. In addition, ezetimibe reduces the cholesterol content of both fasting and postprandial TG -rich lipoproteins, thereby lowering the concentrations of atherogenic remnant particles [154].…”
Section: Management Of Hypertriglyceridemiamentioning
confidence: 99%
“…Ezetimibe has slight positive effects in lowering plasma fasting TG (8%) [153]. In addition, ezetimibe reduces the cholesterol content of both fasting and postprandial TG -rich lipoproteins, thereby lowering the concentrations of atherogenic remnant particles [154].…”
Section: Management Of Hypertriglyceridemiamentioning
confidence: 99%
“…Metaanalysis of 8 randomized, double-blind, placebo-controlled trials revealed that ezetimibe monotherapy for 12 weeks for the treatment of primary hypercholesterolemia was associated with a statistically significant reduction of the mean plasma LDL cholesterol levels by 18.58% as compared with a placebo 42) . Altmann and coworkers revealed Niemann-Pick C1-like 1 (NPC1L1) as a strong candidate for the ezetimibesensitive cholesterol transporter 43,44) .…”
Section: Novel Strategy For the Treatment Of Sitosterolemia With Ezetmentioning
confidence: 99%
“…Other systematic reviews conducted so far have typically been focused on surrogate parameters rather than patient-relevant endpoints. Furthermore, most studies included in these reviews were short, lasting only a few weeks (11)(12)(13)(14)(15)(16)(36)(37)(38). The authors of a comparable review (17), also focusing on patientrelevant endpoints, arrived at the conclusion that, based on the available evidence, no additional or fewer benefits and no greater or lesser harm can be attributed to ezetimibe-statin combination therapy.…”
Section: Discussionmentioning
confidence: 99%